2018
DOI: 10.1002/lt.25034
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy outcomes following liver transplantation is predicted by renal function

Abstract: Liver transplantation (LT) is a successful treatment for both acute liver failure and end-stage liver disease. The number of women of reproductive age undergoing LT is increasing. Pregnancy outcomes are favorable, but there is still a lack of prognostic markers. We aimed to identify factors predictive of adverse pregnancy outcomes in LT recipients. An analysis of all pregnancies occurring in LT recipients from 1989 to 2016 at King's College Hospital was performed. Clinical data of 162 conceptions in 93 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
1
32
1
Order By: Relevance
“…Overall, maternal deaths have not been reported to be higher in pregnant LT recipients when compared with the general population . Death rates during pregnancy and the postpartum phase vary between 0% and 1% . In the older studies quoting higher rates of maternal death (5%‐17%), most deaths occurred more than a year postpartum and were unlikely to be related to the pregnancy .…”
Section: Maternal Outcomesmentioning
confidence: 97%
See 4 more Smart Citations
“…Overall, maternal deaths have not been reported to be higher in pregnant LT recipients when compared with the general population . Death rates during pregnancy and the postpartum phase vary between 0% and 1% . In the older studies quoting higher rates of maternal death (5%‐17%), most deaths occurred more than a year postpartum and were unlikely to be related to the pregnancy .…”
Section: Maternal Outcomesmentioning
confidence: 97%
“…Rates of pre‐eclampsia in the general US population have previously been reported as 4% . Older studies in pregnant LT recipients have reported pre‐eclampsia rates of 21%‐26%, whereas newer studies have reported rates of 7%‐12% . Rates may have improved over time as a result of better management of immunosuppression and risk factors (Table ) associated with pre‐eclampsia.…”
Section: Maternal Outcomesmentioning
confidence: 99%
See 3 more Smart Citations